Utilizing renewable energy, technology, and education for industry 5.0 - Al-Humairi, Safaa 1985- (IGI Global, 2024)
In the tumultuous period of Industrial Revolution 5.0, a pressing challenge confronts our global community: exploring the intricate interplay between technology, education, and renewable energy. As we stand at the cusp of transformative change, the relentless pace of technological evolution, coupled with the imperative to foster sustainable practices, demands a profound understanding of the synergies and challenges inherent in this dynamic landscape. Utilizing Renewable Energy, Technology, and Education for Industry 5.0 emerges as a compelling solution, offering a comprehensive guide tailored for academic scholars seeking clarity amidst the complexities of this revolutionary wave.The rapid convergence of technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and automation, alongside the critical need for renewable energy integration and a paradigm shift in education, presents a multifaceted challenge. Industry leaders grapple with the transformation of processes, educators seek to align curricula with the demands of Industry 5.0, and environmental advocates strive for sustainable solutions. This intricate dance of innovation, education reform, and environmental consciousness requires a comprehensive approach to unraveling complexities, fostering collaboration, and navigating ethical considerations.